Proceedings From the 1st International Conference "Current Concepts and Controversies in Gynecologic and Urologic Oncology". Issue 1 (January 2018) - Matylevich, Olga; Mavrichev, Sergey; Pletnev, Andrei; Evmenenko, Alesya; Shevchuk, Aleksey; Suslova, Valentina; Taranenko, Sergey; Dolomanova, Elena; Rovsky, Dmitry; Portyanko, Anna; Brown, Jubilee; Naumann, Robert Wendel; et al.
Abstract : Abstract: The N.N. Alexandrov National Cancer Center of Belarus organized a collaborative international conference entitled "Current Concepts and Controversies in Gynecologic and Urologic Oncology" with the International Gynecologic Cancer Society and the United States National Cancer Institute. International, regional, and national experts presented recent developments and local conditions in the treatment of gynecologic cancers. Findings were reviewed with the intent of optimizing the management of women with gynecologic cancers across the Commonwealth of Independent States region. At the end of the conference, a resolution was adopted to identify areas for improvement and future collaborations.